Impact of hospital payment reform on rational use of antibiotics: a natural experiment - Zou, Kun; Peng, XiaoFan; Huang, Yue; Shi, JinMin; He, ZhongCheng; Hao, YiJia; Liu, ChaoJie; Tang, Yong; Zhao, ShaoYang; Jiang, YongMu; Choonara, Imti; Zhang, LingLi (Frontiers in Public Health, 2025)
IntroductionWhile numerous studies have examined the effects of diagnosis-related groups (DRG) payment on hospital healthcare, evidence regarding its impact on the quality of hospital healthcare is poor and findings have been inconsistent. This study evaluates how DRG payment reform influences rational use of antibiotics in hospital using the World Health Organization (WHO) Access, Watch, Reserve (AWaRe) classification in China.MethodsWe employed a natural experiment design with difference-in-differences analysis, comparing 10 hospitals implementing DRG payment in two pilot cities with 27 hospitals maintaining fee-for-service (FFS) payment in three control cities in Sichuan Province. Using medicine consumption data from 2016 to 2020 (185 hospital-years), we assessed total antibiotic use/expenditure, Access/Watch group proportions, and Access-to-Watch ratios.ResultsCompared with FFS payment, DRG payment had no significant impact on the total quantity or expenditure of antibiotic use. However, DRG payment led to −13.01% (95% CI: −25.32% to - 0.70%) reduction of proportion of Access antibiotics use and 13.90% (95% CI: 1.97 to 25.83%) increase of proportion Watch antibiotics use. Subgroup analysis showed similar results in both secondary and tertiary hospitals, but greater in the former.DiscussionTDRG hospital payment reform may not affect the total quantity or expenditure of antibiotics use, but decrease the proportion of WHO Access antibiotics use and increase the Watch antibiotics use. Close monitoring and interventions are warranted to improve rational use of antibiotics for health systems during hospital payment reform.